2022
DOI: 10.1051/0004-6361/202142965
|View full text |Cite
|
Sign up to set email alerts
|

Formation of NaCl by radiative association in interstellar environments

Abstract: Context. Radiative association is a possible way of sodium chloride (NaCl) formation in interstellar and related environments. Theoretical studies are essential since laboratory experiments are unavailable and difficult to perform. Aims. The total rate coefficient was calculated for the formation of NaCl by radiative association at 30–750 K. Methods. We included two contributing processes for the total rate-coefficient computation. One of them takes the nonadiabatic coupling between the two lowest 1Σ+ states, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…2, where the cross section is shown from 0.03 eV to 4.6 eV (up to 0.8 eV, the cross section is taken from ref. 11). With increasing collision energy, resonances occur on the cross-section function more frequently until they cease around the threshold 1.4845 eV where the ionic channel opens.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2, where the cross section is shown from 0.03 eV to 4.6 eV (up to 0.8 eV, the cross section is taken from ref. 11). With increasing collision energy, resonances occur on the cross-section function more frequently until they cease around the threshold 1.4845 eV where the ionic channel opens.…”
Section: Resultsmentioning
confidence: 99%
“…3. For completeness, the results from 80 K to 750 K, taken from Šimsová-Zámečníková et al , 11 are also shown in the figure. The values of individual rate coefficients increase with increasing temperature.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations